Accumulation of metal trace elements in different body parts of terrestrial Roman snail Helix pomatia L., 1758 on three polluted sites in Serbia - Rašković, Božidar; Poleksić, Vesna; Jarić, Ivan; Skorić, Stefan; Topisirović, Goran; Stojnić, Bojan (Environmental science and pollution research international, 2023)
Atmospheric pollution remains one of the growing concerns in the twenty-first century, with particular focus on metal trace elements (MTE) from anthropogenic sources, due to their adverse effects on biota. The concentration and type of MTE in the atmosphere and in the soil are diverse, depending on the origin of pollutants, which can cause diverse detrimental effects on organisms living in the nearby environment. Three sites in Central Serbia with different origins of MTE pollution (urban contamination, smelting, and fly ash area) were assessed, using terrestrial Roman snails (Helix pomatia) as biomarker organisms. These snails are sentinel organisms and are known for their capacities for accumulation of MTE. Snails were sampled and their body was divided in three parts: viscera, foot, and shell and concentrations of MTE were determined in each of these body parts using inductively coupled plasma optical spectrometry. Results showed contrasting MTE accumulation patterns in body parts of the snails. Of three studied sites, snails sampled in the vicinity of fly ash containment had lower concentrations of MTE compared to other two polluted sites.
Keywords: Metals; Urban pollution; Biomarker; Snails; látky znečišťující půdu; kovy; Trace Elements; popel uhelný; Bioaccumulation; Smelting; Serbia; Srbsko; hlemýždi; Helix (hlemýždi); Soil Pollutants; Animals; Helix, Snails; zvířata; ICP-OES; Terrestrial snails; Helix pomatia; stopové prvky; Fly ash containment; Coal Ash